Collaborative Approaches to Mitigating Teacher Shortages: Evidence from a Systematic Literature Review - Amelia Febriana; Sugiarto Sugiarto; Siti Zulaikha; Kamaludin Kamaludin (Universitas Pendidikan Mandalika, 2026)
This study aims to examine policy frameworks and collaborative strategies implemented across different countries to address teacher shortages through pre-service teacher education. A systematic literature review method was conducted following the PRISMA 2020 guidelines, analyzing 32 open-access journal articles published between 2020 and 2025 and indexed in the Scopus and Google Scholar databases. The review identified three dominant policy approaches: (1) intensive pre-service programs that actively involve prospective teacher candidates; (2) transitional substitution strategies implemented through short-term policies, such as the utilization of retired teachers and regional incentive schemes; and (3) tripartite structural integration among universities, schools, and government institutions. Data were analyzed using bibliometric techniques to map research trends and thematic structures, followed by qualitative thematic synthesis to examine policy models and collaborative mechanisms. The findings indicate that cross-institutional collaboration plays a crucial role in establishing a sustainable and coherent teacher policy ecosystem. The study concludes that teacher shortages should be addressed through long-term, institutionally grounded policies that strengthen pre-service teacher education pathways. These results provide a conceptual foundation for enhancing Indonesia’s Pre-Service Teacher Internship Program (Program Magang Mahasiswa Calon Guru / PMMCG) as an evidence-based strategy for teacher recruitment, preparation, and professionalization.